Exploring women’s empowerment using a mixed methods approach - Doss, Cheryl; Rubin, Deborah (International Food Policy Research Institute, 2021)
Interest in the meaning and measurement of women’s empowerment has become a stated goal of many programs in international development. This paper explores a collaborative process of studying women’s empowerment in agricultural research for development using both quantitative and qualitative methods. It draws on three bodies of research around empowerment, growing interest in qualitative methods, and measurement research, especially the conceptualization and adaptations of the Women’s Empowerment in Agriculture Index. Employing mixed methods over more than a decade of cooperation among researchers from the Global South and the Global North has challenged the methods and findings of each approach. The work has led to new insights about gender differences in what empowerment means to women and to men, the importance of context, interrelationships among dimensions of empowerment, and the need for greater precision in terms and measures, particularly around decision-making, asset ownership, and time use. Such collaborative research benefits from a long timeframe to build trust and shared understandings across disciplines. The paper concludes with suggestions for the next phase of research.